PEMBENTUKAN KARAKTER DISIPLIN SISWA MELALUI HAFALAN JUZ AMMA DI MI BUSTANUL ULUM MLOKOREJO KECAMATAN PUGER KABUPATEN JEMBER - Sitti Ernawati; Agus Zainudin (FAJAR Jurnal Pendidikan Islam, 2024)
This research was motivated by the habit of disciplinary attitudes at MI Bustanul Ulum Mlokorejo Puger, Jember, where habituation is carried out by providing an example or being a role model for younger classmates and when learning in class begins to take place and also outside the classroom. In collecting data, researchers used observation, interviews and documentation methods, which were used to collect data regarding the condition of the school, the condition of its infrastructure, and the habit of disciplinary attitudes. Discipline will arise if there is openness, cooperation, compliance with norms with a sense of responsibility. Meanwhile, learning is a process of change that is obtained from the efforts made by a person to obtain a new change in behavior as a whole as a result of his own experience in interaction with his environment. The results of this research show that children will have a disciplined character if they are accustomed to waiting their turn in sequence and not going ahead of each other when entering the study room. Likewise, when learning activities are finished, children are accustomed to waiting for their turn, and other good habits that make student disciplined based on the habits they have made.